Surface compatible modified ammonium polyphosphate flame retardant nylon material and method of making same

CN122978697APending Publication Date: 2026-10-27DONGYING JINBANG TAIXIN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611419399.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,上述措施若彼此独立实施,仍难以形成从聚磷酸铵聚合状态控制、低小分子组分控制、颗粒尺度控制到颗粒表面与尼龙树脂之间界面构建的连续技术链

Benefits of technology

本发明通过对聚磷酸铵的缩聚反应过程进行控制,并结合干燥氨气持续通入、反应最高温度控制以及分阶段降温处理,使所得聚磷酸铵的平均聚合度稳定在1200100,同时控制5%质量浓度水悬浊液电导率小于500S/cm、热分解温度高于300℃,再经气流粉碎将中值粒径D50控制在13m以下,达到降低低聚合度及可迁移小分子组分影响、提高聚磷酸铵热稳定性和颗粒分散均匀性的效果,使聚磷酸铵能够更好地适应尼龙材料的高温熔融加工过程,降低加工过程中因聚磷酸铵过早分解、析出或者局部团聚而对材料性能造成的不利影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978697A_ABST
    Figure CN122978697A_ABST
Patent Text Reader

Abstract

The application relates to the field of high polymer materials, and discloses a surface compatible modified ammonium polyphosphate flame-retardant nylon material and a preparation method thereof; the surface compatible modified ammonium polyphosphate flame-retardant nylon material comprises nylon resin and surface compatible modified ammonium polyphosphate; the average polymerization degree of ammonium polyphosphate particles is 1200100, the median particle size D50 is not greater than 13 m, the conductivity of a 5% mass concentration water suspension liquid is less than 500 S / cm, and the thermal decomposition temperature is higher than 300 DEG C. A siloxane anchoring layer and a polyamide compatible chain layer are formed on the surface of the ammonium polyphosphate particles in sequence, and a polyamide oligomer with an end amino group is connected to the surface of the ammonium polyphosphate particles by ring-opening reaction with an epoxy reaction group in the siloxane anchoring layer. During preparation, ammonium polyphosphate particles are obtained by controlled polycondensation, dry ammonia gas introduction, staged temperature reduction and airflow crushing, and then silane hydrolysis condensation, polyamide oligomer grafting and melt blending with the nylon resin are sequentially carried out.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials, specifically to a surface-compatible modified ammonium polyphosphate flame-retardant nylon material and its preparation method. Background Technology

[0002] Ammonium polyphosphate is a class of halogen-free flame retardants with phosphorus and nitrogen as the main flame-retardant active components. It features high phosphorus content, relatively low raw material cost, and low pollution during production, and can be an important component in nitrogen-phosphorus intumescent flame retardant systems. In the flame-retardant modification of nylon materials, introducing ammonium polyphosphate into nylon resin allows it to participate in the condensed-phase flame-retardant process using its phosphorus-containing structure. However, since nylon materials typically undergo high-temperature melting processing, the thermal stability, particle dispersion state, and interfacial compatibility of the flame retardant with the nylon resin directly affect subsequent processing stability and overall material performance. Customer feedback also indicates that high-temperature processing conditions place high demands on the decomposition temperature, precipitation state, and small molecule component control of ammonium polyphosphate.

[0003] Existing ammonium polyphosphate is not a single substance with a completely uniform degree of polymerization; rather, it typically contains polyphosphate components with varying degrees of polymerization. The end-group state and degree of polymerization distribution lead to differences in material properties. When the content of low-polymerization-degree components or hydrolyzable, migratable small-molecule components in ammonium polyphosphate is high, it tends to exhibit poor thermal stability and high ion migration tendency under high-temperature processing conditions, potentially causing precipitation, interfacial defects, or adverse effects on the electrical properties of the composite material. Furthermore, ammonium polyphosphate is an inorganic particle, and its surface chemistry differs from that of the continuous nylon resin phase. If it is added to nylon resin solely through mechanical mixing, particle agglomeration, insufficient local wetting, and inadequate bonding between particles and the resin interface can easily occur during melt blending. Therefore, simply increasing the amount of ammonium polyphosphate added or using ordinary surface coupling treatment is insufficient to simultaneously address the issues of the thermal stability of ammonium polyphosphate, particle size control, and nylon interfacial compatibility.

[0004] To address the aforementioned issues, existing technologies typically involve improving the degree of polymerization of ammonium polyphosphate, reducing particle size, adding nitrogen-based flame-retardant synergistic components, and coupling modification of the flame retardant surface. Customer-provided solutions also involve compounding ammonium polyphosphate with flame-retardant components such as melamine polyphosphate, melamine cyanurate, piperazine pyrophosphate, and nano-silica, and using silanes, aluminates, or other coupling systems for compatibility modification. However, if these measures are implemented independently, it remains difficult to form a continuous technology chain from controlling the polymerization state of ammonium polyphosphate, controlling low-molecular-weight components, controlling particle size, to constructing the interface between the particle surface and nylon resin. Therefore, how to further construct a surface-compatible structure with nylon resin based on obtaining ammonium polyphosphate particles with high polymerization degree, low electrical conductivity, and high thermal stability, and adapt it to the high-temperature melt processing of nylon, remains a technical problem that needs to be solved in this field. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a surface-compatible modified ammonium polyphosphate flame-retardant nylon material and its preparation method, thereby solving the technical problems existing in the prior art.

[0006] The above-mentioned technical objective of the present invention is achieved through the following technical solution: A surface-compatible modified ammonium polyphosphate flame-retardant nylon material includes nylon resin and surface-compatible modified ammonium polyphosphate dispersed in the nylon resin. The surface-compatible modified ammonium polyphosphate includes ammonium polyphosphate particles, a siloxane anchoring layer formed on the surface of the ammonium polyphosphate particles, and a polyamide compatible chain layer connected to the outside of the siloxane anchoring layer. The average degree of polymerization of the ammonium polyphosphate particles is 1200-100, and the median particle size D50 is not greater than 13 μm. The siloxane anchoring layer contains a siloxane structure formed by the hydrolysis and condensation of an epoxy-containing organosilane; the polyamide compatible chain layer is formed by a polyamide oligomer with terminal amino groups, which are connected to the siloxane anchoring layer through a hydroxylamine linking group formed by ring-opening of the epoxy group in the epoxy-containing organosilane with its terminal amino groups. Polyamide oligomers have polyamide segments, and the melting peak temperature of polyamide oligomers is lower than that of nylon resin.

[0007] Preferably, the conductivity of a 5% mass concentration aqueous suspension of ammonium polyphosphate particles is less than 500 S / cm, and the thermal decomposition temperature is higher than 300℃.

[0008] Preferably, the nylon resin is one or a combination of PA6 and PA66; the polyamide oligomer is one of PA6 oligomer, PA66 oligomer, PA610 oligomer with terminal amino groups, or a copolymer oligomer formed from polyamide structural units, the number average molecular weight of the polyamide oligomer is 800 to 3500, and the melting peak temperature of the polyamide oligomer is 15 to 60°C lower than that of the nylon resin.

[0009] Preferably, the epoxy-containing organosilane is glycidyl etheroxypropyltrimethoxysilane; based on 100 parts by weight of ammonium polyphosphate particles, the epoxy-containing organosilane is 1 to 6 parts by weight, and the polyamide oligomer is 2 to 10 parts by weight; based on 100 parts by weight of nylon resin, the surface-compatible modified ammonium polyphosphate is 8 to 20 parts by weight.

[0010] Preferably, it further includes a flame retardant synergist component co-dispersed in the nylon resin with surface-compatible modified ammonium polyphosphate, wherein the flame retardant synergist component is selected from at least one of melamine polyphosphate, melamine cyanurate and piperazine pyrophosphate.

[0011] Preferably, it also includes nano-silica, wherein the nano-silica is dispersed together with surface-compatible modified ammonium polyphosphate and flame-retardant synergistic components in nylon resin.

[0012] A method for preparing a surface-compatible modified ammonium polyphosphate flame-retardant nylon material includes: S1: Mix diammonium hydrogen phosphate, ammonium dihydrogen phosphate and phosphorus pentoxide for polycondensation reaction. During the polycondensation reaction, dry ammonia gas is introduced and the reaction temperature is controlled. After the polycondensation is completed, the reactants are cooled in stages to obtain ammonium polyphosphate with an average degree of polymerization of 1200-100. S2: Ammonium polyphosphate is subjected to air jet milling and particle size classification to obtain ammonium polyphosphate particles with a median particle size D50 of not more than 13m; S3: Hydrolyze the epoxy-containing organosilane, so that the hydrolysis product comes into contact with the ammonium polyphosphate particles and condenses on the surface of the ammonium polyphosphate particles to form a siloxane anchoring layer with epoxy reactive groups. Then, separate the ammonium polyphosphate particles with the siloxane anchoring layer from the treatment medium containing free organosilane and dry them. S4: The dried ammonium polyphosphate particles with a siloxane anchoring layer are mixed with polyamide oligomers with terminal amino groups, so that the terminal amino groups of the polyamide oligomers react with the epoxy reactive groups in the siloxane anchoring layer to undergo a ring-opening reaction, forming a polyamide compatible chain layer connected to the siloxane anchoring layer through -hydroxyamine linking groups on the outside of the siloxane anchoring layer, thus obtaining surface-compatible modified ammonium polyphosphate. S5: Surface-compatible modified ammonium polyphosphate is melt-blended with nylon resin to disperse the surface-compatible modified ammonium polyphosphate in the nylon resin. After extrusion, cooling and pelletizing, flame-retardant nylon material with surface-compatible modified ammonium polyphosphate is obtained.

[0013] Preferably, in step S1, diammonium hydrogen phosphate, ammonium dihydrogen phosphate and phosphorus pentoxide are fed into a kneading reaction device, the material temperature is raised to 200°C and then dry ammonia gas is introduced at a flow rate of 7-9 g / s, and the maximum material temperature of the polycondensation reaction is controlled at 3105°C by the cooling and temperature control structure of the kneading reaction device. After the polycondensation reaction is completed, the material is cooled from 310°C to 240°C within 30 minutes and discharged. Then, the material is cooled from 240°C to 140°C within 40 minutes.

[0014] Preferably, in step S3, the ammonium polyphosphate particles are first dried at 100-120°C, and an epoxy-containing organosilane is added to a mixed medium formed by ethanol and water and adjusted to acidity, so that the epoxy-containing organosilane is hydrolyzed to form silanol groups, and then the silanol groups are condensed on the surface of the ammonium polyphosphate particles. Subsequently, the obtained solid is separated from the mixed medium, washed and dried. In step S4, the dried ammonium polyphosphate particles with a siloxane anchoring layer are mixed with polyamide oligomers at 140–190°C, so that the polyamide oligomers form a molten flow state and undergo a ring-opening reaction.

[0015] Preferably, in step S5, the melting peak temperature of the polyamide oligomer is 15–60°C lower than that of the nylon resin. A twin-screw extruder is used for melt blending. Along the material conveying direction, the polyamide compatible chain layer is sequentially brought into a molten state, the nylon resin is made into a continuous melt, and the surface-compatible modified ammonium polyphosphate is melt-mixed with the continuous melt. Then, the mixture is extruded, cooled, and pelletized.

[0016] In summary, the present invention has the following main beneficial effects: This invention controls the polycondensation reaction process of ammonium polyphosphate, combined with continuous introduction of dry ammonia gas, control of the maximum reaction temperature, and staged cooling treatment, to stabilize the average degree of polymerization of the obtained ammonium polyphosphate at 1200-100. At the same time, it controls the conductivity of the 5% mass concentration water suspension to be less than 500 S / cm and the thermal decomposition temperature to be higher than 300℃. Then, it controls the median particle size D50 to be below 13 μm through air jet milling. This achieves the effects of reducing the influence of low degree of polymerization and migratable small molecule components, improving the thermal stability and particle dispersion uniformity of ammonium polyphosphate, and enabling ammonium polyphosphate to better adapt to the high-temperature melting process of nylon materials. It also reduces the adverse effects on material properties caused by premature decomposition, precipitation, or local agglomeration of ammonium polyphosphate during processing.

[0017] This invention first forms a siloxane anchoring layer with epoxy reactive groups on the surface of ammonium polyphosphate particles, and then performs a ring-opening reaction between the ammonium polyphosphate particles with the siloxane anchoring layer and a polyamide oligomer with terminal amino groups. The polyamide oligomer is fixed to the outside of the siloxane anchoring layer through hydroxylamine linking groups and forms a polyamide compatible chain layer, thereby achieving the effect of constructing a stable transition interface between inorganic ammonium polyphosphate particles and organic nylon resin. This reduces the tendency of ammonium polyphosphate particles to debond and aggregate in the nylon matrix, and improves its dispersion and interfacial bonding state in nylon resin while maintaining the flame retardant effect of ammonium polyphosphate.

[0018] This invention selects polyamide oligomers with a melting peak temperature 15–60°C lower than that of nylon resin, and during the twin-screw melt blending process, ensures that the polyamide compatible chain layer enters the molten or high-segment active state before the nylon resin, and then fully mixes with the nylon resin to form a continuous melt. This achieves the effect of pre-wetting and stable dispersion of surface-compatible modified ammonium polyphosphate during the melting process of the nylon body. Furthermore, by combining melamine polyphosphate, melamine cyanurate, piperazine pyrophosphate, and flame-retardant synergistic components in nano-silica, a synergistic effect can be formed on the basis of the nitrogen-phosphorus flame-retardant system, thereby taking into account the flame-retardant performance, thermal stability, and processing adaptability of the material. Attached Figure Description

[0019] Figure 1 This is a flowchart of the method of the present invention. Detailed Implementation

[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0021] refer to Figure 1 A surface-compatible modified ammonium polyphosphate flame-retardant nylon material and its preparation method are disclosed. The flame-retardant nylon material uses nylon resin as the continuous phase and surface-compatible modified ammonium polyphosphate as the flame-retardant dispersed phase. The surface-compatible modified ammonium polyphosphate is mainly composed of ammonium polyphosphate particles obtained by controlled polycondensation, and a siloxane anchoring layer and a polyamide compatible chain layer are sequentially formed on the surface of the ammonium polyphosphate particles.

[0022] The ammonium polyphosphate particles have an average degree of polymerization of 1200-100 and a median particle size D50 of no more than 13 μm. Furthermore, the conductivity of its 5% mass concentration aqueous suspension is less than 500 S / cm, and the thermal decomposition temperature is higher than 300 °C.

[0023] The siloxane anchoring layer is formed by the hydrolysis of an epoxy-containing organosilane, followed by surface condensation with ammonium polyphosphate particles. After the first stage of treatment, the ammonium polyphosphate particles with the siloxane anchoring layer are separated from the treatment medium containing free organosilane, washed, and dried before undergoing the second stage of treatment. The second stage utilizes a polyamide oligomer with terminal amino groups. The ring-opening reaction between the terminal amino groups and the epoxy reactive groups retained in the siloxane anchoring layer forms hydroxylamine linking groups, allowing the polyamide oligomer to attach to the outside of the siloxane anchoring layer, thereby forming a polyamide compatible chain layer.

[0024] The siloxane anchoring layer does not require the formation of a dense coating film with the same thickness and complete continuity. The basis for this determination is that after the first stage of treatment and washing, the surface of the ammonium polyphosphate particles still has a stable silicon-containing structure, while retaining epoxy reactive groups that can be used for the second stage reaction.

[0025] The polyamide compatible chain layer is not required to form a complete film layer that can be independently peeled off from the ammonium polyphosphate particles. Instead, it refers to at least a portion of the polyamide oligomer chain being fixed to the outside of the siloxane anchoring layer after undergoing a ring-opening reaction with the aforementioned epoxy reactive groups through the terminal amino groups, and forming an interface region containing polyamide chain segments on the particle surface.

[0026] The average degree of polymerization is a characterization of the average length of the ammonium polyphosphate molecular chain after the polycondensation reaction is completed, and is not a parameter formed by subsequent air jet milling, silane treatment or nylon melt processing.

[0027] Different batches of ammonium polyphosphate were compared using the same method for detecting the average degree of polymerization. The ^31P nuclear magnetic resonance (NMR) method was preferred for quantitative analysis of terminal phosphorus and total phosphorus. During detection, the ammonium polyphosphate to be tested was converted into a test system that met the requirements of NMR detection and did not produce significant further hydrolysis. Terminal phosphorus and intra-chain phosphorus signals were obtained and integrated under the same test conditions.

[0028] For samples characterized by average linear ammonium polyphosphate chains, the average degree of polymerization is determined according to the following formula: In the formula, The average degree of polymerization of ammonium polyphosphate; This represents the total integral value corresponding to all phosphorus structures in the sample. It is the sum of the integral values ​​corresponding to the two end phosphorus structures.

[0029] Parallel testing was conducted on the same batch, and the average value of the parallel test results was used as the average degree of polymerization of the batch of ammonium polyphosphate. A test result between 1100 and 1300 indicates that the average degree of polymerization of 1200-100 as described in this application is met.

[0030] When using other established and calibrated methods for detecting the average degree of polymerization of ammonium polyphosphate, all examples and comparative examples should use the same detection system, and values ​​obtained from different methods should not be mixed in the same set of data.

[0031] The 5% mass concentration aqueous suspensions in this application are all prepared according to the mass percentage concentration.

[0032] Weigh 5.00g of dried ammonium polyphosphate granules and add 95.00g of deionized water to make the total mass of ammonium polyphosphate and water 100.00g. Stir at 251℃ to make the granules uniformly dispersed in the water. Then, measure the conductivity using a conductivity meter calibrated with a standard solution under the same stirring and testing time conditions.

[0033] The same deionized water, the same test temperature, and the same electrode constant were used in the examples, comparative examples, and different production batches. A conductivity value less than 500 S / cm meets the conductivity requirements of this application.

[0034] This conductivity is a measured value of the ion migration state of ammonium polyphosphate under uniform aqueous phase conditions. It is not used to directly calculate the content of a specific low-polymerization degree phosphate, nor is it used as a substitute for the inability to measure small molecule components.

[0035] To avoid different interpretations of thermal decomposition temperature due to different definitions of thermal analysis, this application uniformly adopts thermogravimetric analysis for determination.

[0036] Dry ammonium polyphosphate samples of the same mass range were taken and subjected to thermogravimetric analysis under nitrogen protection at a uniform heating rate. This application uses the temperature at which the sample mass decreases by 5% relative to the dry basis mass at the start of heating as the thermal decomposition temperature, i.e., T5%.

[0037] Therefore, a thermal decomposition temperature higher than 300°C, in this embodiment, means that the T5% measured under the above-mentioned unified TGA conditions is greater than 300°C.

[0038] When formally generating implementation data, the T5% value obtained from the actual thermogravimetric curve should be directly cited, without calculating the thermal decomposition temperature based on the degree of polymerization or theoretical composition.

[0039] Diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and phosphorus pentoxide are used as phosphorus-containing raw materials.

[0040] Since the two ammonium phosphate components in the original production record are adjusted in a linked manner, this embodiment can use a molar ratio of 1.0:1.0:2.0 for diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and phosphorus pentoxide as a specific implementation point for illustration. This ratio is used to illustrate how those skilled in the art can implement this method, but this application does not use the specific molar ratio of the three raw materials as the boundary of the scope of protection.

[0041] Polycondensation is carried out using kneading reaction equipment with heating, kneading, and cooling temperature control functions. When using a 2000L kneader, the 2000L only indicates the equipment specification; the actual feed weight of each raw material is calculated proportionally according to the above molar relationship and the equipment's allowable feed weight.

[0042] After the raw materials are fed into the kneading reaction equipment, they are mixed and heated. When the temperature of the reactants reaches 200°C, dry ammonia gas is continuously introduced.

[0043] The mass flow rate of dried ammonia is controlled at 7–9 g / s. Here, 7–9 g / s is the mass flow rate of ammonia measured in the inlet pipeline of the reaction equipment, controlled by a calibrated mass flow meter.

[0044] During the ammonia feeding process, the material undergoes further condensation and heating. The maximum material temperature is limited by the cooling and temperature control structure set in the kneading reaction equipment, keeping the maximum material temperature at 3105℃, i.e., 305~315℃.

[0045] The 3105℃ refers to the main temperature of the reactant material, not the set temperature of the heating jacket. The temperature sensing element is located in a position that can reflect the temperature of the main material, and the same temperature measuring position is used in different production batches.

[0046] The polycondensation stage continues until the resulting ammonium polyphosphate reaches an average degree of polymerization of 1100–1300. During production, the batch reaction time can be controlled using established protocols, and the average degree of polymerization can be confirmed by periodically sampling and rapidly cooling the samples. Once the aforementioned average degree of polymerization is reached, further heating is stopped, and a controlled cooling process begins.

[0047] After the polycondensation is complete, the material is cooled from approximately 310°C to 240°C within 30 minutes and then discharged. This 30 minutes refers to the time elapsed from the start of this active cooling phase until the main material temperature reaches 240°C.

[0048] The material is then transferred to a cooling chamber, where it is cooled from 240°C to 140°C within 40 minutes. The definition of 40 minutes is the same as that of 30 minutes mentioned above.

[0049] The cooled ammonium polyphosphate is then fed into an air jet mill for pulverization and particle size classification.

[0050] The pressure, feed rate, and classifier parameters of the air jet mill are adjusted according to the specific equipment specifications; therefore, a fixed rotational speed corresponding to a particular equipment model is not considered a necessary technical feature. The endpoint of the process is determined by a median particle size D50 obtained from laser particle size analysis that is not greater than 13 μm.

[0051] The D50 referred to in this application is the median particle size calculated based on volume distribution, that is, the particle size corresponding to a cumulative volume fraction of 50%.

[0052] After the air jet milling is completed, the obtained ammonium polyphosphate is tested for average degree of polymerization, electrical conductivity, D50 and thermal decomposition temperature.

[0053] The batches used for subsequent surface compatibility modification meet the following requirements: The average degree of polymerization is 1200-100; D5013m; The conductivity of a 5% (w / v) aqueous suspension is <500 S / cm; T5% > 300℃.

[0054] The average degree of polymerization is mainly formed by the aforementioned polycondensation process, D50 is mainly formed by air jet milling and classification, and electrical conductivity and thermal decomposition temperature are used as batch quality inspection indicators after polycondensation and milling are completed. The air jet milling process is not interpreted as a process step to increase the degree of polymerization or generate a high thermal decomposition temperature.

[0055] Ammonium polyphosphate particles that meet the above batch conditions are selected and pre-dried at 100–120°C to reduce the influence of adsorbed water on the particle surface on the hydrolysis and condensation process of organosilanes.

[0056] 100–120℃ is the material handling temperature of the drying equipment. The actual drying time is determined based on the loading amount, material layer thickness, and equipment vacuum or ventilation status. The process judgment that drying is complete is based on the result of two consecutive stable sampling and weighing, rather than using a uniform drying time that is unrelated to equipment specifications as the boundary.

[0057] The preferred epoxy-containing organosilane is glycidyl etheroxypropyltrimethoxysilane, i.e., KH560.

[0058] Based on 100 parts by weight of dried ammonium polyphosphate particles before surface modification, the amount of KH560 added is 1 to 6 parts by weight, more preferably 2 to 4 parts by weight.

[0059] First, add KH560 to a mixed medium consisting of ethanol and deionized water, and adjust the system to a weakly acidic state with acetic acid, preferably controlling the pH at 4-6, so that the hydrolyzable groups of KH560 will hydrolyze to form silanol groups, while retaining as much of the epoxy groups as possible for the second stage reaction.

[0060] The pH here is measured directly using a calibrated pH meter, without resorting to methods that cannot determine the boundary, such as using an appropriate amount of acid or weak acidity.

[0061] After KH560 completes pre-hydrolysis, dried ammonium polyphosphate particles are added. Under continuous mixing conditions, the hydrolyzed organosilanes are allowed to fully contact the surface of the ammonium polyphosphate particles. The silanol groups are adsorbed on the particle surface and undergo condensation. At the same time, some silanols undergo condensation between themselves, thereby forming a surface layer containing a siloxane structure.

[0062] After the first stage of surface treatment is completed, the solid particles are first separated from the liquid treatment medium, and then the resulting solid is washed and dried.

[0063] The solid-liquid separation is a necessary process step before the second-stage reaction. The polyamide oligomer is not directly added to the first-stage treatment medium, which still contains a large amount of free KH560.

[0064] The particles, after separation, washing, and drying, are used as the first-stage intermediates and proceed to the next processing step.

[0065] To confirm that the first stage was not only due to the adhesion of free KH560, sample A of untreated ammonium polyphosphate and sample B after the first stage of treatment, washing and drying were retained respectively.

[0066] FTIR and XPS analyses were performed on samples A and B under the same conditions.

[0067] When a stable Si surface signal is still detected on sample B after washing, relative to sample A, and it can still be confirmed that the epoxy structure has not been completely consumed, it can be confirmed that a siloxane anchoring layer for the next stage reaction has been formed on the surface of the first-stage intermediate.

[0068] Since the specific infrared peak position can be affected by the testing method, sample preparation method and instrument resolution, a single fixed wavenumber is not used as the sole criterion for judging the protection range. Instead, it is confirmed by the changes in the spectrum of the sample before and after treatment under the same conditions and the continuous structural changes produced by the subsequent second-stage reaction.

[0069] The first-stage intermediate was subjected to a second-stage treatment using polyamide oligomers with terminal amino groups.

[0070] Polyamide oligomers can be PA6 oligomers, PA66 oligomers, PA610 oligomers with terminal amino groups, or copolymer oligomers formed from polyamide structural units.

[0071] The number-average molecular weight (Mn) of polyamide oligomers ranges from 800 to 3500.

[0072] In this application, Mn is uniformly determined using a gel permeation chromatography method suitable for polyamides. The same solvent system, chromatographic column, calibration system, and data processing method are used in the same set of examples and comparative examples. Batch data provided by raw material suppliers can be used as a basis for raw material screening, but formal experimental data are verified using the same method to reduce numerical differences caused by different detection systems.

[0073] The polyamide oligomer was also confirmed to have terminal amino groups capable of participating in the epoxy ring-opening reaction. These terminal amino groups can be confirmed by polyamide end-group titration or by end-group analysis methods suitable for this oligomer.

[0074] Based on 100 parts by weight of the original dry ammonium polyphosphate particles, the amount of polyamide oligomer added is 2 to 10 parts by weight, more preferably 3 to 7 parts by weight.

[0075] The dried intermediate obtained in the first stage was heated and mixed with the polyamide oligomer.

[0076] For polyamide oligomers whose melt flow temperature is compatible with the process, the second-stage treatment temperature is 140–190°C. The actual temperature within this range is determined based on the DSC melt behavior of the polyamide oligomer used, and should at least ensure that the oligomer has a melt flow state capable of wetting the particle surface.

[0077] After the polyamide oligomer melts and contacts the siloxane anchoring layer, its terminal amino group undergoes nucleophilic ring-opening with the epoxy reactive groups retained in the anchoring layer, forming a hydroxyl-containing amine linkage structure between the two, wherein the -hydroxylamine linkage group is...

[0078] This reaction does not require the complete conversion of all epoxy groups in the siloxane anchoring layer, nor does it require all terminal amino groups of each polyamide oligomer molecule to participate in the reaction. As long as at least a portion of the polyamide oligomer chains are stably linked to the outside of the siloxane anchoring layer through the ring-opening reaction, a polyamide compatible chain layer is formed.

[0079] The sample after the second stage reaction is completed is designated as sample C.

[0080] Sample C was first subjected to washing or extraction to remove unreacted free polyamide oligomers, and then subjected to FTIR, XPS and necessary thermal analysis under the same conditions as sample B.

[0081] Since ammonium polyphosphate itself contains nitrogen, the presence of nitrogen cannot be used as the sole evidence for the formation of a polyamide compatible chain layer.

[0082] The following changes should be considered when making a judgment: the epoxy structure retained in the first-stage sample undergoes a change consistent with the ring-opening reaction after the second stage; the second-stage sample shows amide structure signals of polyamide segments; and after the removal of free oligomers, the polyamide-related structure still exists on the particle surface.

[0083] The composition of the reactants, the two-stage reaction sequence, and the above characterization results jointly confirm the interfacial structure formed on the outside of the ammonium polyphosphate particles, consisting of a siloxane anchoring layer, hydroxylamine linking groups, and a polyamide compatible chain layer.

[0084] The nylon resin used is one of PA6 and PA66 or a combination of both.

[0085] Before use, DSC tests were performed on both the polyamide oligomer and the nylon resin. The same test procedure was used for both, and the first heating, cooling and second heating were completed under nitrogen protection. The main melting endothermic peak in the second heating curve was taken as the melting peak temperature.

[0086] Assume the melting peak temperature of nylon resin is The melting peak temperature of polyamide oligomers is The temperature difference of the melting peak is: ; In the formula, This represents the difference in melting peak temperature between nylon resin and polyamide oligomer, expressed in °C. This refers to the melting peak temperature of nylon resin, expressed in degrees Celsius (C). The melting peak temperature of the polyamide oligomer is expressed in °C.

[0087] Select one that meets the 15℃ requirement Material combination at 60℃.

[0088] Therefore, 15–60°C is not an artificially set scoring threshold, but rather the result of DSC measurements of the actual polyamide oligomer and nylon resin, calculated using the difference mentioned above.

[0089] When a combination of PA6 and PA66 is used and two distinct major melt peaks are formed on the DSC curve, the lower major melt peak corresponding to the initial formation of the bulk continuous melt of the nylon blend resin is taken as the... The benchmark for comparison.

[0090] Based on 100 parts by weight of dry nylon resin, the amount of surface-compatible modified ammonium polyphosphate added is 8 to 20 parts by weight.

[0091] The 8–20 parts by weight represent the total mass of the modified particles after the construction of the siloxane anchoring layer and the polyamide compatible chain layer.

[0092] In contrast, 1-6 parts by weight of KH560 and 2-10 parts by weight of polyamide oligomers are measured based on 100 parts by weight of dried ammonium polyphosphate particles before surface treatment.

[0093] Therefore, this application has two clear and independent weight calculation bases, which are not used interchangeably.

[0094] Depending on the specific application requirements of the flame-retardant material, flame-retardant synergistic components can be further added to the nylon resin.

[0095] The flame retardant synergistic component is selected from at least one of melamine polyphosphate, melamine cyanurate, and piperazine pyrophosphate.

[0096] The flame-retardant synergistic component, together with the surface-modified ammonium polyphosphate, enters the nylon molten system without replacing the aforementioned siloxane anchoring layer or polyamide compatible chain layer.

[0097] Furthermore, nano-silica can be added. Nano-silica, as an independent solid component, is dispersed in nylon resin together with surface-compatible modified ammonium polyphosphate and flame-retardant synergistic components.

[0098] Nano-silica and the siloxane anchoring layer formed on the surface of ammonium polyphosphate particles are two different technologies. The former is added to flame-retardant nylon material as an independent particle, while the latter is the surface interface structure of the ammonium polyphosphate particles themselves.

[0099] The dried nylon resin and surface-compatible modified ammonium polyphosphate are fed into a twin-screw extruder.

[0100] Along the material conveying direction, the process sequentially forms a solid conveying stage, a polyamide compatible chain layer pre-melting stage, a nylon resin main body melting stage, and a melt mixing stage.

[0101] Based on the aforementioned DSC measurements and The barrel temperature zone is set so that the material temperature before entering the molten zone of the nylon resin body is higher than the temperature required for the polyamide oligomer to form a molten flow state, while being lower than the temperature required for the nylon resin to form a continuous melt.

[0102] Therefore, the polyamide compatible chain layer already connected to the surface of the ammonium polyphosphate particles first enters the molten or high-segment active state.

[0103] As the material continues to be conveyed downstream, the temperature of the barrel rises to the normal melting and processing range of the nylon resin, causing the nylon resin to form a continuous melt and allowing the polyamide compatible chain layer, which is already in a molten state, to come into full contact with the nylon melt.

[0104] The polyamide compatible chain layer entering the molten state is a physical state change of the polyamide chain segments, and does not mean that the aforementioned ring-opening connection structure formed by the terminal amino and epoxy groups is broken. Therefore, the polyamide compatible chain layer maintains its connection with the siloxane anchoring layer during melt blending, while its outer polyamide chain segments can undergo interfacial contact and interdiffusion with the nylon continuous phase.

[0105] The melt is then further melt-mixed to disperse the surface-compatible modified ammonium polyphosphate in the continuous nylon phase. The melt is then extruded, cooled, and pelletized to obtain a surface-compatible modified ammonium polyphosphate flame-retardant nylon material.

[0106] The twin-screw speed and feed rate are adjusted according to the extruder screw diameter, length-to-diameter ratio and actual production capacity, with the process control conditions being that the material can be stably conveyed, the nylon is fully plasticized and there is no obvious long-term high-temperature retention. The fixed screw speed corresponding to a certain equipment model is not a necessary limitation of this application.

[0107] Example 1 The feed was prepared by using a molar ratio of diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and phosphorus pentoxide of 1.0:1.0:2.0.

[0108] After the material temperature reaches 200℃, dry ammonia gas is introduced, with the ammonia mass flow rate controlled at 7-9 g / s. The maximum material temperature is controlled at 3105℃ through a cooling and temperature control structure. Polycondensation ends after the target average degree of polymerization is reached. The material is then cooled to 240℃ within 30 minutes and discharged. Finally, it is cooled to 140℃ within 40 minutes in a cooling chamber.

[0109] The obtained ammonium polyphosphate was pulverized and classified by air jet mill, and batches of ammonium polyphosphate that met the following requirements were selected: average degree of polymerization 1200-100, D50 13m, conductivity of 5% mass concentration water suspension <500S / cm, and T5% >300℃.

[0110] Ammonium polyphosphate particles were dried at 100–120°C. Based on 100 parts by weight of dried ammonium polyphosphate particles, 3 parts by weight of KH560 were added, and the particles were pre-hydrolyzed in a weakly acidic ethanol / water system for the first stage of treatment. After treatment, solid-liquid separation, washing, and drying were performed.

[0111] Subsequently, 5 parts by weight of a polyamide oligomer with terminal amino groups were added based on the original 100 parts by weight of dried ammonium polyphosphate granules. The Mn of this polyamide oligomer was 800–3500, and its melting peak temperature was confirmed by DSC to be 15–60°C lower than that of the PA6 used.

[0112] A second-stage treatment was performed at a temperature within the range of 140–190°C that allowed the polyamide oligomer to form a molten flow state. This allowed the terminal amino groups to undergo a ring-opening reaction with the epoxy reactive groups in the siloxane anchoring layer on the surface of the ammonium polyphosphate particles, resulting in surface-compatible modified ammonium polyphosphate.

[0113] Based on 100 parts by weight of dry PA6, 12 parts by weight of the obtained surface-compatible modified ammonium polyphosphate were added, and the mixture was melt-blended, extruded, cooled and pelletized using the aforementioned twin-screw temperature progressive method to obtain a surface-compatible modified ammonium polyphosphate flame-retardant PA6 material.

[0114] Example 2 The polycondensation, ammonia induction, maximum temperature control, staged cooling and air jet milling methods for ammonium polyphosphate are the same as those in Example 1.

[0115] Select ammonium polyphosphate particles that meet the requirements for average degree of polymerization, electrical conductivity, particle size and thermal decomposition temperature. Add 1 part by weight of KH560 to 100 parts by weight of dry ammonium polyphosphate particles to complete the first stage of treatment, and then add 2 parts by weight of terminal amino polyamide oligomer to complete the second stage of treatment.

[0116] Based on 100 parts by weight of PA6, 8 parts by weight of the obtained surface-compatible modified ammonium polyphosphate were added for melt blending.

[0117] This embodiment corresponds to an implementation state where KH560 is 1 part by weight, polyamide oligomer is 2 parts by weight, and surface compatibility modified ammonium polyphosphate is 8 parts by weight. This is to clarify that the lower limit of each range has the same continuous preparation path as in Example 1, rather than only intermediate preferred points that can be implemented.

[0118] Example 3 PA66 was used as the nylon resin.

[0119] The preparation method of ammonium polyphosphate is the same as in Example 1. Based on 100 parts by weight of dried ammonium polyphosphate particles, 6 parts by weight of KH560 are added to complete the first stage of treatment, and then 10 parts by weight of polyamide oligomer with terminal amino groups are added to carry out the second stage of treatment.

[0120] DSC tests were performed on PA66 and polyamide oligomers used in practice, and a combination was selected that satisfies the requirement that the melting peak temperature of the polyamide oligomer is 15-60℃ lower than that of PA66.

[0121] Based on 100 parts by weight of dried PA66, 20 parts by weight of the obtained surface-compatible modified ammonium polyphosphate were added for twin-screw melt blending.

[0122] For this PA66 system, the specific barrel temperature of the twin-screw extruder is reset based on the actual melting peak temperature of PA66, rather than directly applying the temperature of the PA6 system. Along the material conveying direction, the sequence of the polyamide compatible chain layer first entering the molten state, followed by PA66 forming a continuous melt, and then the two continuing to melt and mix is ​​maintained.

[0123] This embodiment is used to support the upper limit of the range of 6 parts by weight of KH560, 10 parts by weight of polyamide oligomer and 20 parts by weight of surface-compatible modified ammonium polyphosphate.

[0124] Example 4 The surface-compatible modified ammonium polyphosphate prepared in Example 1 was used, and melamine polyphosphate was further added as a flame retardant synergist.

[0125] Surface-compatible modified ammonium polyphosphate, melamine polyphosphate, and dried PA6 are uniformly premixed before entering the twin-screw extruder, and then extruded according to the aforementioned melt processing sequence.

[0126] Melamine polyphosphate exists as an independent flame-retardant synergist, does not participate in the formation of the first-stage siloxane anchoring layer on the surface of ammonium polyphosphate particles, nor does it serve as a substitute for the second-stage amino-terminated polyamide oligomers.

[0127] Melamine polyphosphate can also be replaced with melamine cyanurate or piperazine pyrophosphate, or a combination of two or more of them.

[0128] Example 5 Based on Example 4, nano-silica was further added.

[0129] Nano-silica is premixed with surface-compatible modified ammonium polyphosphate, flame-retardant synergist and nylon resin, and then fed into a twin-screw extruder.

[0130] Nano-silica is dispersed as an independent solid component in the continuous phase of nylon resin in the obtained material; the siloxane anchoring layer formed on the surface of ammonium polyphosphate particles is still formed by the hydrolysis and condensation of epoxy-containing organosilanes, and the two are independent of each other in terms of material composition and formation mode.

[0131] To provide a unified evaluation of the structural characteristics, thermal stability, flame retardant properties, and mechanical properties of the materials obtained in each embodiment, the materials obtained in Examples 1 to 5 were tested under the same sample conditioning conditions and testing methods.

[0132] For ammonium polyphosphate particles entering the surface treatment step, the average degree of polymerization, median particle size D50, conductivity of a 5% mass concentration aqueous suspension, and thermal decomposition temperature T5% were measured. The average degree of polymerization was determined using the aforementioned ^31P nuclear magnetic resonance method; D50 was determined using laser particle size analysis; the conductivity of the 5% mass concentration aqueous suspension was determined using the aforementioned test system consisting of 5.00g of ammonium polyphosphate particles and 95.00g of deionized water; and T5% was determined using the aforementioned thermogravimetric analysis method. Only batches of ammonium polyphosphate that simultaneously meet the following requirements—an average degree of polymerization of 1200×100, a D50 not greater than 13 μm, a conductivity of a 5% mass concentration aqueous suspension less than 500 S / cm, and a T5% higher than 300℃—enter the subsequent surface modification step.

[0133] For ammonium polyphosphate particles that have undergone the first-stage siloxane anchoring treatment and surface-compatible modified ammonium polyphosphate particles that have undergone the second-stage polyamide oligomer grafting treatment, FTIR and XPS detection were performed, respectively. The particles after the first-stage treatment were used to confirm that the silicon-containing structure remained stable after washing and retained the epoxy reactive groups for the second-stage reaction. For the particles after the second-stage treatment, after removing free polyamide oligomers, changes in the epoxy structure and amide structure signals of the polyamide segments were detected to determine the formation state of the polyamide compatible chain layer.

[0134] DSC analysis was performed on the polyamide oligomer and the corresponding nylon resin to obtain their melting peak temperatures. It was confirmed that the melting peak temperature of the polyamide oligomer was 15–60°C lower than that of the corresponding nylon resin. In Examples 1, 2, 4, and 5, when PA6 was used, the melting peak temperature of the actual PA6 input was used as the comparison benchmark; in Example 3, when PA66 was used, the melting peak temperature of the actual PA66 input was used as the comparison benchmark.

[0135] The resulting flame-retardant nylon materials were subjected to tests for vertical burning performance, limiting oxygen index, tensile properties, flexural properties, and notched impact properties. Simultaneously, the cross-sections of the samples were observed using a scanning electron microscope. The molding equipment, sample size, conditioning time, and testing conditions were kept consistent across all groups of samples to eliminate the influence of differences in sample preparation conditions on the comparison results.

[0136] Example 1 characterizes the material state when KH560, polyamide oligomer, and surface-compatible modified ammonium polyphosphate are all within the defined ranges; Example 2 characterizes the material state when the above components are close to the defined lower limit; Example 3 characterizes the material state when the above components are close to the defined upper limit and PA66 is used as the nylon resin. Since the type of nylon resin in Example 3 is different from that in Examples 1 and 2, its flame retardancy and mechanical properties are used to illustrate the feasibility of the PA66 system, and the quality of the treatment agent addition is not directly evaluated using absolute values ​​compared to the PA6 system.

[0137] Example 4 uses the same surface-compatible modified ammonium polyphosphate and PA6 system as Example 1. The difference is that Example 4 further adds a flame-retardant synergist. Therefore, the comparison between Example 4 and Example 1 is used to evaluate the changes in flame-retardant performance and mechanical properties before and after the addition of the flame-retardant synergist. Example 5 further adds nano-silica to Example 4. Therefore, the comparison between Example 5 and Example 4 is used to evaluate the changes in flame-retardant performance, thermal stability, and material mechanical properties before and after the addition of nano-silica.

[0138] To evaluate the interfacial effects generated by the polyamide compatible chain layer itself, comparative samples were also set up. The first comparative sample used the same batch of ammonium polyphosphate particles and PA6 as in Example 1, but the ammonium polyphosphate particles were not surface-treated; the second comparative sample used the same first-stage siloxane anchoring treatment as in Example 1, but without the second-stage grafting of terminal amino polyamide oligomers; the third comparative sample used the same amount of siloxane anchoring treated ammonium polyphosphate and polyamide oligomers as in Example 1, but the polyamide oligomers were not pre-grafted with the siloxane anchoring layer, but were added as a free component during the nylon melt blending stage. The effective amount of ammonium polyphosphate added in each comparative sample remained consistent with that in Example 1.

[0139] The test results between Example 1 and the first comparative sample are used to compare the material state differences between unmodified surface-modified ammonium polyphosphate and two-stage surface-compatible modified ammonium polyphosphate; the test results between Example 1 and the second comparative sample are used to compare the interface differences between samples with only a siloxane anchoring layer and samples with a polyamide compatible chain layer; the test results between Example 1 and the third comparative sample are used to distinguish the differences between two treatment methods: adding polyamide oligomers as a free component and pre-connecting them to the surface of ammonium polyphosphate particles through a ring-opening reaction.

[0140] The test results for each embodiment and comparative sample were recorded according to the same test items. For ammonium polyphosphate raw material, the average degree of polymerization, D50, conductivity of 5% mass concentration water suspension, and T5% were recorded; for surface-treated particles, the FTIR and XPS characterization results were recorded; and for the final nylon material, the vertical burning performance, limiting oxygen index, tensile strength, flexural strength, notched impact strength, and cross-sectional interface morphology were recorded. Specific performance values ​​are subject to the actual test report.

[0141] The surface-compatible modified ammonium polyphosphate flame-retardant nylon materials obtained in each embodiment were tested for vertical burning performance, limiting oxygen index, tensile properties, flexural properties, and notched impact properties under the same sample preparation conditions. The interface state between the ammonium polyphosphate particles and the nylon resin in the material cross-section was observed using a scanning electron microscope. For Examples 1-5 and the comparative samples, the same batch of corresponding nylon resin, the same calculation caliber for effective ammonium polyphosphate content, the same sample conditioning conditions, and the same testing methods were used to ensure the comparability of the test results.

[0142] In this study, Example 1 was compared with the untreated ammonium polyphosphate system to evaluate the differences in material state before and after the two-stage surface compatibility modification. Example 1 was also compared with a system that only formed a siloxane anchoring layer without a polyamide compatibility chain layer to evaluate the influence of the polyamide compatibility chain layer on the particle interface state. Furthermore, Example 1 was compared with a system in which polyamide oligomers were directly added to nylon resin as a free component to distinguish between two treatment methods: surface chemical bonding of polyamide oligomers and ordinary melt blending. Actual performance evaluation results are based on the test data of the corresponding batches.

[0143] In this application, 1200100, <500S / cm, >300℃, D5013m, 200℃, 7~9g / s, 3105℃, 30min and 40min all correspond to the actual production and batch control technical conditions of ammonium polyphosphate. The first four items form batch release indicators for polymerization state, electrical conductivity state, thermal stability state and particle size, respectively, while the latter five items correspond to the equipment control conditions for polycondensation and cooling processes.

[0144] 1–6 parts by weight of KH560 and 2–10 parts by weight of polyamide oligomers fall within the feeding range for surface treatment of ammonium polyphosphate particles, and are uniformly measured using 100 parts by weight of dry ammonium polyphosphate particles as the measurement standard; 8–20 parts by weight of surface-compatible modified ammonium polyphosphate are uniformly measured using 100 parts by weight of dry nylon resin as the measurement standard.

[0145] Mn of 800–3500 falls within the raw material characterization range of polyamide oligomers, determined by GPC; 15–60℃ represents the raw material combination relationship between nylon resin and polyamide oligomers, calculated by DSC measurements of both separately; 140–190℃ is the defined temperature range for further second-stage processing, applicable only if the selected polyamide oligomer can form a molten flow state within this temperature range.

[0146] The obtained material can be further tested under uniform conditions for vertical combustion performance, limiting oxygen index, tensile properties, flexural properties, notched impact performance, and performance retention rate before and after hydrothermal treatment; at the same time, SEM can be used to observe the interface state between ammonium polyphosphate particles and nylon resin in the cross-section of the material.

[0147] All examples and comparative samples should use the same batch of nylon resin, the same calculation caliber for effective ammonium polyphosphate content, the same sample preparation conditions, and the same testing methods.

[0148] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A surface-compatible modified ammonium polyphosphate flame-retardant nylon material, comprising nylon resin and surface-compatible modified ammonium polyphosphate dispersed in the nylon resin, characterized in that: The surface-compatible modified ammonium polyphosphate includes ammonium polyphosphate particles, a siloxane anchoring layer formed on the surface of the ammonium polyphosphate particles, and a polyamide compatible chain layer connected to the outside of the siloxane anchoring layer. The average degree of polymerization of the ammonium polyphosphate particles is 1200-100, and the median particle size D50 is not greater than 13 μm. The siloxane anchoring layer contains a siloxane structure formed by the hydrolysis and condensation of an epoxy-containing organosilane; the polyamide compatible chain layer is formed by a polyamide oligomer with terminal amino groups, which are connected to the siloxane anchoring layer through a hydroxylamine linking group formed by ring-opening of the epoxy group in the epoxy-containing organosilane with its terminal amino groups. Polyamide oligomers have polyamide segments, and the melting peak temperature of polyamide oligomers is lower than that of nylon resin.

2. The surface-compatible modified ammonium polyphosphate flame-retardant nylon material according to claim 1, characterized in that: The conductivity of a 5% mass concentration aqueous suspension of ammonium polyphosphate particles is less than 500 S / cm, and the thermal decomposition temperature is higher than 300℃.

3. The surface-compatible modified ammonium polyphosphate flame-retardant nylon material according to claim 2, characterized in that: The nylon resin is one of PA6 and PA66 or a combination of both; the polyamide oligomer is one of PA6 oligomer, PA66 oligomer, PA610 oligomer with terminal amino groups or a copolymer oligomer formed from polyamide structural units, the number average molecular weight of the polyamide oligomer is 800 to 3500, and the melting peak temperature of the polyamide oligomer is 15 to 60°C lower than that of the nylon resin.

4. The surface-compatible modified ammonium polyphosphate flame-retardant nylon material according to claim 3, characterized in that: The epoxy-containing organosilane is glycidyl etheroxypropyltrimethoxysilane; based on 100 parts by weight of ammonium polyphosphate particles, the epoxy-containing organosilane is 1 to 6 parts by weight, and the polyamide oligomer is 2 to 10 parts by weight; based on 100 parts by weight of nylon resin, the surface-compatible modified ammonium polyphosphate is 8 to 20 parts by weight.

5. The surface-compatible modified ammonium polyphosphate flame-retardant nylon material according to claim 4, characterized in that: It also includes a flame-retardant synergist component co-dispersed in the nylon resin with surface-compatible modified ammonium polyphosphate, the flame-retardant synergist component being selected from at least one of melamine polyphosphate, melamine cyanurate and piperazine pyrophosphate.

6. The surface-compatible modified ammonium polyphosphate flame-retardant nylon material according to claim 5, characterized in that: It also includes nano-silica, which is dispersed in nylon resin together with surface-compatible modified ammonium polyphosphate and flame-retardant synergistic components.

7. A method for preparing a surface-compatible modified ammonium polyphosphate flame-retardant nylon material, applicable to the surface-compatible modified ammonium polyphosphate flame-retardant nylon material according to any one of claims 1-6, characterized in that, include: S1: Mix diammonium hydrogen phosphate, ammonium dihydrogen phosphate and phosphorus pentoxide for polycondensation reaction. During the polycondensation reaction, dry ammonia gas is introduced and the reaction temperature is controlled. After the polycondensation is completed, the reactants are cooled in stages to obtain ammonium polyphosphate with an average degree of polymerization of 1200-100. S2: Ammonium polyphosphate is subjected to air jet milling and particle size classification to obtain ammonium polyphosphate particles with a median particle size D50 of not more than 13m; S3: Hydrolyze the epoxy-containing organosilane, so that the hydrolysis product comes into contact with the ammonium polyphosphate particles and condenses on the surface of the ammonium polyphosphate particles to form a siloxane anchoring layer with epoxy reactive groups. Then, separate the ammonium polyphosphate particles with the siloxane anchoring layer from the treatment medium containing free organosilane and dry them. S4: The dried ammonium polyphosphate particles with a siloxane anchoring layer are mixed with polyamide oligomers with terminal amino groups, so that the terminal amino groups of the polyamide oligomers react with the epoxy reactive groups in the siloxane anchoring layer to undergo a ring-opening reaction, forming a polyamide compatible chain layer connected to the siloxane anchoring layer through -hydroxyamine linking groups on the outside of the siloxane anchoring layer, thus obtaining surface-compatible modified ammonium polyphosphate. S5: Surface-compatible modified ammonium polyphosphate is melt-blended with nylon resin to disperse the surface-compatible modified ammonium polyphosphate in the nylon resin. After extrusion, cooling and pelletizing, flame-retardant nylon material with surface-compatible modified ammonium polyphosphate is obtained.

8. The method for preparing a surface-compatible modified ammonium polyphosphate flame-retardant nylon material according to claim 7, characterized in that: In step S1, diammonium hydrogen phosphate, ammonium dihydrogen phosphate and phosphorus pentoxide are fed into the kneading reaction equipment. After the material temperature is raised to 200°C, dry ammonia gas is introduced at a flow rate of 7-9 g / s. The maximum material temperature of the polycondensation reaction is controlled at 3105°C by the cooling and temperature control structure of the kneading reaction equipment. After the polycondensation reaction is completed, the material is cooled from 310°C to 240°C within 30 minutes and discharged. Then, the material is cooled from 240°C to 140°C within 40 minutes.

9. The method for preparing a surface-compatible modified ammonium polyphosphate flame-retardant nylon material according to claim 8, characterized in that: In step S3, the ammonium polyphosphate particles are first dried at 100-120°C. An epoxy-containing organosilane is added to a mixed medium formed by ethanol and water and adjusted to acidity to hydrolyze the epoxy-containing organosilane to form silanol groups. The silanol groups are then condensed on the surface of the ammonium polyphosphate particles. The resulting solid is then separated from the mixed medium, washed, and dried. In step S4, the dried ammonium polyphosphate particles with a siloxane anchoring layer are mixed with polyamide oligomers at 140–190°C, so that the polyamide oligomers form a molten flow state and undergo a ring-opening reaction.

10. The method for preparing a surface-compatible modified ammonium polyphosphate flame-retardant nylon material according to claim 9, characterized in that: In step S5, the melting peak temperature of the polyamide oligomer is 15–60°C lower than that of the nylon resin. A twin-screw extruder is used for melt blending. Along the material conveying direction, the polyamide compatible chain layer is sequentially brought into a molten state, the nylon resin is made into a continuous melt, and the surface-compatible modified ammonium polyphosphate is melt-mixed with the continuous melt. Then, the mixture is extruded, cooled, and pelletized.